Manajemen Ulkus Diabetikum Terhadap Family Care Giver Pasien Diabetes Melitus Di Wilayah Tanjung Raya Bandar Lampung - Khomsah, Ida Yatun; Nurani, Rahmawati Dian (Yayasan Inspirasi El Burhani, 2025)
Introduction: Diabetic foot ulcers are one of the main detrimental complications and serious conditions of diabetes mellitus, where 10% to 25% of diabetes mellitus patients develop diabetic foot ulcers. This can be done by caring for diabetic feet and wounds through Family Caregiver management. Patients can control blood sugar levels independently anywhere and anytime. Considering the current situation, it is necessary to provide health education on the management of diabetic foot and wound care to prevent more severe complications in diabetes mellitus patients. Objective: To increase the knowledge and ability to care for family members in carrying out wound care and foot care for Diabetes Mellitus patients. Method: The method of this activity is carried out using lecture, discussion, demonstration and question and answer methods. Result: Knowledge before giving the material was good knowledge of 6 people (30%) and sufficient knowledge of 14 people (70%), while after giving the material knowledge increased to good knowledge of 19 people (95%) and sufficient knowledge of 5 people (5 %). Overall, the counseling starting from the pre-test and post-test had a positive impact. Conclusion: The results of the evaluation given to participants showed an increase in knowledge and skills in providing foot and wound care for families with diabetes.